Influencia de los programas de bienestar social en el clima laboral de los colaboradores de la empresa fitopan s.r.l., año 2014 - Vidal Pozo, Rosa Mercedes (2015)
This thesis makes research on the relationship between Social Welfare Programs and influence of these in the working environment of the employees of the company Fitopan SRL. The techniques used were direct observation, interview, survey and using references. Also, the type of research was not experimental level of quantitative and qualitative research. In that sense, concepts of quality of life, sense of belonging, job performance and welfare of workers was investigated. These concepts were used, described and analyzed with respect to the relationship you have on the working environment. It is hypothesized that the lack of a social welfare program adversely affects the working environment of the employees of the company; that is, that through the implementation of social welfare programs, policies and practices that respect the human condition of their workers, an improvement is achieved in the effectiveness and efficiency of the organization, better management of the human factor, as well as greater opportunities for people to make their work a chance to dignity. To this end, also managed to understand the perceptions and motivations of the individual to his work, and then determine the degree of impact on the work environment; and how these incidents arising in situations of labor disputes, low job performance, quality of life and sense of belonging. It is hoped that this research will serve as a reference for implementing appropriate business strategies to enhance the working environment of human capital as a key factor every business and treated well become your greatest competitive advantage for the success of any.